Immunotherapy and Radioimmunotherapy for Desmoplastic Small Round Cell Tumor - Espinosa-Cotton, Madelyn; Cheung, Nai-Kong V. (Frontiers in Oncology, 2021)
Desmoplastic small round cell tumor (DRSCT) is a highly aggressive primitive sarcoma that primarily affects adolescent and young adult males. The 5-year survival rate is 15-30% and few curative treatment options exist. Although there is no standard treatment for DSRCT, patients are most often treated with a combination of aggressive chemotherapy, radiation, and surgery. Targeted therapy inhibitors of PDGFA and IGF-1R, which are almost uniformly overexpressed in DSRCT, have largely failed in clinical trials. As in cancer in general, interest in immunotherapy to treat DSRCT has increased in recent years. To that end, several types of immunotherapy are now being tested clinically, including monoclonal antibodies, radionuclide-conjugated antibodies, CAR T cells, checkpoint inhibitors, and bispecific antibodies (BsAbs). These types of therapies may be particularly useful in DSRCT, which is frequently characterized by widespread intraperitoneal implants, which are difficult to completely remove surgically and are the frequent cause of relapse. Successful treatment with immunotherapy or radioimmunotherapy following debulking surgery could eradiate these micrometasteses and prevent relapse. Although there has been limited success to date for immunotherapy in pediatric solid tumors, the significant improvements in survival seen in the treatment of other pediatric solid tumors, such as metastatic neuroblastoma and its CNS spread, suggest a potential of immunotherapy and specifically compartmental immunotherapy in DSRCT.